Factors Associated with Leg Ulcers in Adults with Sickle Cell Disease in Brazil. (February 2023) - Reis de Souza, Valquíria; Kelly, Shannon; Cerdeira Sabino, Ester; Mendes de Oliveira, Franciane; Silva, Tassila; Miranda Teixeira, Carolina; Máximo, Claudia; Loureiro, Paula; Barbara de Freitas Carneiro-Proietti, Anna; Gomes, Isabel; Custer, Brian; de Almeida-Neto, Cesar
ABSTRACT: OBJECTIVE: To define the prevalence of leg ulcers and identify the clinical and laboratory factors associated with leg ulcers in adult participants. METHODS: The authors conducted a cross-sectional study of 1, 109 patients who were 18 years or older with SS or Sβ 0 -thalassemia genotypes from a Brazilian cohort. Investigators assessed the prevalence of factors associated with leg ulcers from 2013 to 2017. RESULTS: The prevalence of leg ulcers was 21%. Increasing age (odds ratio [OR], 1.07; range, 1.06–1.09), male sex (OR, 2.03; range, 1.44–2.87), treatment with chronic transfusion therapy (OR, 1.88; range, 1.15–3.03), higher indirect bilirubin levels (OR, 1.48; range, 1.02–2.16), and low hemoglobin levels (OR, 2.17; range, 1.52–3.11) were associated with leg ulcers. Participants who self-reported as Black (OR, 6.75; range, 2.63–21.32), mixed (OR, 3.91; range, 1.55–12.20), and other/unknown (OR, 3.84; range, 1.04–15.24) were more likely to have leg ulcers compared with those who self-reported as White. CONCLUSIONS: The prevalence of leg ulcers in this Brazilian cohort was higher than the prevalence reported in developed countries. Known factors such as age and male sex were corroborated. The increased bilirubin level and decreased hemoglobin levels among participants with leg ulcers support the hypothesis that hemolysis is correlated with leg ulcer pathogenesis. Self-reported black skin color was an independent predictor of leg ulcers and warrants further study to understand the etiology and implications of this finding.